2020
DOI: 10.3390/ijerph17186758
|View full text |Cite
|
Sign up to set email alerts
|

Association between Presenteeism, Psychosocial Aspects of Work and Common Mental Disorders among Nursing Personnel

Abstract: Presenteeism is the term used to describe going in to work even with a health problem. The phenomenon has been identified as one prior factor in sickness absence and, accordingly, the better it is understood, the better will be the prevention strategies. This study aimed to examine the mediating role of presenteeism (the ability to concentrate on work and to complete work despite a health problem) in the association between psychosocial factors at work and common mental disorders (CMD). This cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 50 publications
0
23
0
7
Order By: Relevance
“…Presenteeism refers to working while one is sick and can cause significant productivity losses associated with poor health, emotional exhaustion and workplace epidemics from virus transmission such as the current SARS CoV-2 [ 1 ]. However, the presenteeism literature has been very critical regarding the measurement of presenteeism with recent studies, suggesting the poor psychometric evidence of the current self-reported measures [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presenteeism refers to working while one is sick and can cause significant productivity losses associated with poor health, emotional exhaustion and workplace epidemics from virus transmission such as the current SARS CoV-2 [ 1 ]. However, the presenteeism literature has been very critical regarding the measurement of presenteeism with recent studies, suggesting the poor psychometric evidence of the current self-reported measures [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Occupations in caring, helping, and primary teaching sectors are most prone to presenteeism, suggesting a culture predicated in part on loyalty to and concern for vulnerable clients to a fault (Johns, 2009). Mobilizing OSH resources to alleviate the negative effects of working under illness is of paramount importance for all healthcare professionals, however, targeted solutions are vital given that gender roles influence prevalence of sickness presenteeism among women, and typically lead to worse mental health outcomes as a result (Chen et al, 2021;Gustafson Sendén et al, 2016;Silva-Costa et al, 2020). From an organizational viewpoint, the deeply ingrained "machismo of medicine" and its noxious effects on female health professionals supports Acker's emphasis of gender disparities as the opportunity structure for discrimination.…”
Section: The Set Up: Glimpses Of the Ideal Worker Then And Nowmentioning
confidence: 99%
“…(1,2) O trabalho na área da saúde representa um cenário onde diversos fatores contribuem para o adoecimento dos profissionais, seja em decorrência da complexidade da assistência, das condições de trabalho, o não reconhecimento profissional, baixos salários, além das jornadas longas e exaustivas exigidas pelas instituições de saúde. (3,4) O atendimento em unidades de saúde que integram as redes de atenção às urgências e emergências tem a premissa de garantir o acolhimento de casos agudos ou crônicos agudizados de caráter clínico, psiquiátrico ou traumático, bem como oferecer otimização da assistência à saúde, pois lidam com o inesperado, a instabilidade da vítima, bem como há a necessidade de execução de procedimentos imediatos, aliados ao ritmo de trabalho acelerado. (5,6) A assistência direta ao paciente, realizada pelos trabalhadores de enfermagem que atuam em hospitais e unidades de pronto atendimento aliada às situações de tensão, pode gerar sobrecarga e estresse psíquico, provocando adoecimento do profissional com presença de sintomas físicos e psíquicos.…”
Section: Introductionunclassified